2016
DOI: 10.1186/s12955-016-0544-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimally important difference of the Child Oral Health Impact Profile for children with orofacial anomalies

Abstract: BackgroundThe Child Oral Health Impact Profile (COHIP) is an instrument designed to measure the self-reported oral health-related quality of life of children between the ages of 8 and 15, including domains for oral health, functional well-being, social-emotional well-being, school environment and self-image. The purpose of this study was to estimate the minimally important difference (MID) of the COHIP for patients with cleft lip/palate.MethodsData from a 6-year, prospective, longitudinal cohort study of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…In other research conducted with a subsample of the present participants, MID (minimally important difference) estimates using an anchor-based approach indicated that the minimally important difference for the overall COHIP was 2.95 [35]. Framing the present finding in this manner suggests that the surgical candidates initially rated their OHRQoL as lower than peers without a surgical recommendation and that the improvements over time were modest.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In other research conducted with a subsample of the present participants, MID (minimally important difference) estimates using an anchor-based approach indicated that the minimally important difference for the overall COHIP was 2.95 [35]. Framing the present finding in this manner suggests that the surgical candidates initially rated their OHRQoL as lower than peers without a surgical recommendation and that the improvements over time were modest.…”
Section: Discussionmentioning
confidence: 47%
“…Furthermore, current analyses used tests of statistical significance, which may not capture the true effect of treatment on OHRQoL [51]. Additional reporting of the minimally important difference and clinically meaningful change will be undertaken but is beyond the scope of this paper [27, 35, 52]. Finally, since there was no control group in this study, incorporating population-based assessments like items from the National Survey on Children with Special Health and N-HANES queries as well as generic quality of life surveys would provide worthwhile comparisons [5355] regarding employment, educational attainment, health care utilization, barriers to care and QoL that facilitate group comparisons and elucidate long-term treatment outcomes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the study, some participating children received secondary cleft‐related surgery, while others did not. Further details regarding the study protocol and procedures have been previously published …”
Section: Study Description and Findingsmentioning
confidence: 99%
“…However, a higher number of previous surgical interventions was also associated with lower self‐ and caregiver‐rated OHRQoL scores . Additionally, minimally important differences (MID) for clinically meaningful change were calculated for the study sample using both the anchor‐based and distribution criteria method . These estimates can be used for surgeons and researchers to determine whether surgical intervention for CL/P has had a meaningful impact beyond statistical significance on patients.…”
Section: Study Description and Findingsmentioning
confidence: 99%
See 1 more Smart Citation